All-solid-state lithium ion secondary battery and method for manufacturing same

By forming a low-resistance layer between the negative electrode layer and the separator layer of the all-solid lithium-ion secondary battery, the interface resistance is reduced by using lithium alloy materials, the problem of high battery resistance is solved, and the charge and discharge characteristics and energy density are improved.

CN119923735APending Publication Date: 2025-05-02NAT INST FOR MATERIALS SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380067858.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-09-14
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

It is difficult for existing all-solid lithium-ion secondary batteries to sinter the graphite negative electrode during the manufacturing process, resulting in high resistance and affecting the charge and discharge characteristics.

Method used

By forming a low-resistivity layer between the negative electrode layer and the separator layer, the interface resistance is reduced by using a lithium alloy material. The low-resistive layer may be composed of elements such as gold, silver, platinum, tin, indium, etc., with a thickness ranging from 1 to 500 nm. It is preferably arranged in the ground with the separator layer.

Benefits of technology

It effectively reduces the internal resistance of the battery, improves the charge and discharge characteristics and energy density, and enhances the stability and reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923735A_ABST
    Figure CN119923735A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing an all-solid-state lithium ion secondary battery having excellent charge / discharge characteristics. The present invention has at least a negative electrode layer, a separator layer, and a positive electrode layer, the negative electrode layer containing a negative electrode active material containing graphite, the separator layer comprising an oxide solid electrolyte, and a resistance-reduced layer being formed between the negative electrode layer and the separator layer. The low-resistance layer is composed of a lithium alloy or has a substance that forms a lithium alloy by performing a secondary battery operation that causes a current to flow between the negative electrode layer and the positive electrode layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an all-solid lithium ion secondary battery and a method for manufacturing the same. Background Art

[0002] Large-capacity secondary batteries are used in a variety of applications, including hybrid electric vehicles, energy sources for electronic devices, and storage devices for renewable energy, such as solar cells. In order to realize a low-carbon, smart society, secondary batteries with larger capacity and excellent charge and discharge characteristics are needed.

[0003] Lithium-ion secondary batteries have high energy density. Carbon materials such as graphite are used in the negative electrode to absorb and store lithium ions. In addition, oxides of lithium and transition metals are used in the positive electrode to suppress metal precipitation associated with charging and discharging. Therefore, lithium-ion secondary batteries are highly practical and have become the mainstream of large-capacity secondary batteries. Moreover, as the next generation, all-solid lithium-ion secondary batteries with larger capacity, safety, and excellent handling are expected.

[0004] As lithium ion secondary batteries using a negative electrode made of graphite, there are lithium ion secondary batteries using an organic electrolyte and sulfide-type all-solid lithium ion secondary batteries using a sulfide solid electrolyte.

[0005] The organic electrolyte can be bonded to the graphite negative electrode active material particles with a wide reaction area by infiltrating the porous graphite negative electrode layer. In addition, the sulfide solid electrolyte can also easily obtain the bonding between the electrolyte particles and the bonding between the electrolyte and the active material particles by cold pressing the mixture of the solid electrolyte particles and the graphite negative electrode active material particles.

[0006] As disclosed in Patent Document 1 and Non-Patent Document 1, oxide-type all-solid lithium-ion secondary batteries with high atmospheric stability use high-temperature sintering to make the connection between solid electrolyte particles and between solid electrolyte and active material particles. However, since graphite with high sintering properties is difficult to sinter, it is necessary to use other methods such as crimping to obtain the connection between solid electrolyte and active material particles, making it difficult to make a negative electrode with low resistance and room temperature operation. The negative electrode with high resistance increases the internal resistance of the battery, which has an adverse effect on the charge and discharge characteristics.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent No. 6686945

[0010] Patent Document 2: Japanese Patent No. 6748035

[0011] Non-patent literature

[0012] Non-patent literature 1: Martin Finsterbusch, Timo Danner, Chin-Long Tsai, Sven Uhlenbruck, Arnulf Latz, and Olivier Guillon, ACS Appl. Mater. Interfaces 2018, 10, 22329-22339.

[0013] Non-patent literature 2: Narumi Ohta, Shin Kimura, Junichi Sakabe, KazutakaMitsuishi, Tsuyoshi Ohnishi, and Kazunori Takada, ACS Appl. Energy Mater. 2019, 2, 7005-7008. Summary of the invention

[0014] Problems to be solved by the invention

[0015] An object of the present invention is to provide an all-solid lithium ion secondary battery having excellent charge and discharge characteristics and a method for producing the same.

[0016] Means for solving problems

[0017] The configuration of the present invention for solving the problems is shown below.

[0018] (Composition 1)

[0019] An all-solid-state lithium-ion secondary battery, which is an all-solid-state lithium-ion secondary battery having at least a negative electrode layer, a separator layer, and a positive electrode layer, wherein the negative electrode layer contains a negative electrode active material having graphite, the separator layer contains an oxide solid electrolyte, a low-resistance layer is formed between the negative electrode layer and the separator layer, and the low-resistance layer is composed of a lithium alloy, or has a material that forms a lithium alloy by performing secondary battery operation in which an electric current flows between the negative electrode layer and the positive electrode layer.

[0020] (Composition 2)

[0021] According to the all-solid lithium ion secondary battery described in configuration 1, the low resistance layer contains one or more elements selected from gold, silver, platinum, aluminum, tin, indium, germanium, lead, zinc, antimony, magnesium, silicon, cadmium, gallium, tellurium and bismuth.

[0022] (Composition 3)

[0023] The all-solid lithium ion secondary battery according to Configuration 1, wherein the resistance reducing layer has a thickness of 1 to 500 nm.

[0024] (Composition 4)

[0025] The all-solid lithium ion secondary battery according to Configuration 1, wherein the resistance reducing layer includes one or more selected from the group consisting of gold, silver, platinum, tin, indium, and silicon.

[0026] (Composition 5)

[0027] The all-solid lithium ion secondary battery according to any one of Configurations 1 to 4, wherein the resistance reducing layer and the separator layer are arranged in contact with each other.

[0028] (Composition 6)

[0029] The all-solid lithium ion secondary battery according to any one of Configurations 1 to 5, wherein the resistance reducing layer is arranged in contact with the negative electrode layer.

[0030] (Composition 7)

[0031] The all-solid lithium ion secondary battery according to any one of Configurations 1 to 6, wherein the solid electrolyte contained in the separator layer has a garnet-type or garnet-type-like crystal structure having high ion conductivity.

[0032] (Composition 8)

[0033] An all-solid-state lithium-ion secondary battery according to any one of structures 1 to 7, wherein the solid electrolyte contained in the separator layer is composed of a composite oxide containing Li and one or more selected from ceramics having a garnet-type structure, ceramics having a perovskite-type structure, and ceramics having a LISICON-type structure.

[0034] (Composition 9)

[0035] The all-solid lithium ion secondary battery according to any one of Configurations 1 to 8, wherein the negative electrode active material is composed of graphite.

[0036] (Composition 10)

[0037] The all-solid lithium ion secondary battery according to any one of Configurations 1 to 9, wherein the negative electrode active material includes graphite and a material capable of absorbing less than 10% of lithium ions.

[0038] (Composition 11)

[0039] The all-solid lithium ion secondary battery according to any one of Configurations 1 to 10, wherein the positive electrode contains a positive electrode active material, and the positive electrode active material is composed of one or more selected from the following:

[0040] By LiM 1 x Mn 2-x O4-type lithium manganese composite oxide, wherein M 1is at least one element selected from the group consisting of Li, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Fe, Co, Ni, Cu, Al, Sn, Sb, In, Nb, Mo, W, Y, Ru and Rh, 0.01≤x≤0.5,

[0041] By Li x Mn (1-y-x) Ni y M 2 z O (2-k) F l The layered compound shown, where M 2 is at least one element selected from Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr and W, 0.8≤x≤1.2, 0<y<0.5, 0≤z≤0.5, k+l<1, -0.1≤k≤0.2, 0≤l≤0.1,

[0042] By LiCo 1-x M 3 x A lithium cobalt composite oxide represented by O2, wherein M 3 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5,

[0043] By LiNi 1-x M 4 x A lithium nickel composite oxide represented by O2, wherein M 4 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5,

[0044] By LiM 5 1-x N 1 x PO4 represented by an olivine-type composite oxide, wherein M 5 is at least one element selected from Fe, Mn and Co, N 1 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5,

[0045] Li4Ti5O 12 The lithium titanium composite oxide shown.

[0046] (Composition 12)

[0047] A method for manufacturing an all-solid-state lithium-ion secondary battery according to any one of structures 1 to 11, wherein the low resistance layer is formed by one or more methods selected from sputtering, vapor deposition, coating formation and foil pasting.

[0048] Effects of the Invention

[0049] According to the present invention, an all-solid lithium ion secondary battery having excellent charge and discharge characteristics and a method for producing the same are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a structural explanatory diagram showing the structure of the all-solid lithium ion secondary battery of the present invention in a cross-sectional view.

[0051] Figure 2 This is a structural explanatory diagram showing the structure of an all-solid lithium ion half-cell (hereinafter referred to as a half-cell) of an embodiment in a cross-sectional view.

[0052] Figure 3 This is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 1 (Example 1). Since the description is made from the perspective of the negative electrode of the full cell, the reaction of inserting lithium ions into graphite as the test electrode active material is regarded as the charge reaction, and the reaction of removing lithium ions from graphite as the test electrode active material is regarded as the discharge reaction.

[0053] Figure 4 This is the AC impedance spectrum of the half-cell obtained in Example 1 (Example 1) after the initial charge.

[0054] Figure 5 3 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 2 (Example 2).

[0055] Figure 6 This is a diagram showing an X-ray diffraction pattern of the half-cell obtained in Example 2 (Example 2) after the initial charge.

[0056] Figure 7 This is a graph showing the initial charge and discharge characteristics of the half-cell obtained in Example 3 (Example 3).

[0057] Figure 8 This is a characteristic diagram showing the battery capacity with respect to the number of charge and discharge cycles of the half-cell obtained in Example 3 (Example 3).

[0058] Fig. 9 3 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 4 (Example 4).

[0059] Fig.10 This is the AC impedance spectrum of the half-cell obtained in Example 4 (Example 4) after the initial charge.

[0060] Fig.11 3 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 5 (Example 5).

[0061] Fig.12 This is the AC impedance spectrum of the half-cell obtained in Example 5 (Example 5) after the initial charge.

[0062] Fig.13 3 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 6 (Example 6).

[0063] Fig.14 This is the AC impedance spectrum of the half-cell obtained in Example 6 (Example 6) after the initial charge.

[0064] Fig.15 3 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 7 (Example 7).

[0065] Fig.16 This is the AC impedance spectrum of the half-cell obtained in Example 7 (Example 7) after the initial charge.

[0066] Fig.17 It is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Comparative Example 1 (Example 8).

[0067] Fig.18 This is an AC impedance spectrum of the half-cell obtained in Comparative Example 1 (Example 8) after the initial charge.

[0068] Fig.19 This is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 9 as an embodiment. Since the description is made from the perspective of the negative electrode of the full cell, the reaction of inserting lithium ions into graphite as the test electrode active material is regarded as the charge reaction, and the reaction of removing lithium ions from graphite as the test electrode active material is regarded as the discharge reaction.

[0069] Fig. 20 : is an AC impedance spectrum of the half-cell obtained in Example 9 as an embodiment after the initial charge.

[0070] Fig.21 1 is a diagram showing an X-ray diffraction pattern of a half-cell obtained in Example 9 as an embodiment after initial charge.

[0071] Fig. 22 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 10 as an embodiment.

[0072] Fig.23 This is an AC impedance spectrum of the half-cell obtained in Example 10 as an embodiment after the initial charge.

[0073] Fig.24 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 11 as an embodiment.

[0074] Fig.25 This is an AC impedance spectrum of the half-cell obtained in Example 11 as an embodiment after the initial charge.

[0075] Fig.26 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 12 as an embodiment.

[0076] Fig. 27 This is an AC impedance spectrum of the half-cell obtained in Example 12 as an embodiment after the initial charge.

[0077] Fig.28 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 13 as an embodiment.

[0078] Fig.29 : is an AC impedance spectrum of the half-cell obtained in Example 13 as an embodiment after the initial charge.

[0079] Fig.30 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 14 as an embodiment.

[0080] Fig.31 This is an AC impedance spectrum of the half-cell obtained in Example 14 as an embodiment after the initial charge.

[0081] Fig.32 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 15 as an embodiment.

[0082] Fig.33 This is an AC impedance spectrum of the half-cell obtained in Example 15 as an embodiment after the initial charge.

[0083] Fig.34 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 16 as an embodiment.

[0084] Fig.35 This is an AC impedance spectrum of the half-cell obtained in Example 16 as an embodiment after the initial charge.

[0085] Fig.36 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 17 as an embodiment.

[0086] Fig.37 This is an AC impedance spectrum of the half-cell obtained in Example 17 as an embodiment after the initial charge.

[0087] Fig.38 1 is a characteristic diagram showing the initial charge characteristics of the half-cell obtained in Example 18 as an embodiment.

[0088] Fig.39 This is an AC impedance spectrum of the half-cell obtained in Example 18 as an embodiment after the initial charge.

[0089] Fig.40 1 is a diagram showing an X-ray diffraction pattern of a half-cell obtained in Example 18 as an embodiment after initial charge.

[0090] Fig.41 This is a diagram showing the element distribution in the depth direction of the negative electrode layer obtained in Example 19 as an embodiment. The horizontal axis represents the sputtering time (seconds) and the vertical axis represents the intensity.

[0091] Fig.42 This is a diagram showing the element distribution in the depth direction of the negative electrode layer obtained in Example 20 as an embodiment. The horizontal axis represents the sputtering time (seconds) and the vertical axis represents the intensity. DETAILED DESCRIPTION

[0092] Hereinafter, the embodiment of the present invention will be described with reference to the drawings. It should be noted that AB in the text means A or more and B or less.

[0093] <Battery structure>

[0094] The all-solid lithium ion secondary battery 101 of this embodiment is as follows Figure 1 As shown, it includes a negative electrode collector 11, a negative electrode active material layer 12, a low resistance layer 13, a separator layer 15, a positive electrode active material layer 16, and a positive electrode collector 17. Among them, the negative electrode collector 11 and the negative electrode active material layer 12 constitute a negative electrode (negative electrode layer) 14, and the positive electrode active material layer 16 and the positive electrode collector 17 constitute a positive electrode (positive electrode layer) 18. It should be noted that the negative electrode active material layer 12 and the negative electrode collector 11 do not need to be separated, and the negative electrode active material layer 12 may also have the function of the negative electrode collector 11. In addition, the positive electrode active material layer 16 and the positive electrode collector 17 may not be separated, and the positive electrode active material layer 16 may also have the function of the positive electrode collector 17.

[0095] The negative electrode current collector 11 and the positive electrode current collector 17 (hereinafter, both are collectively referred to as collectors) are formed by contacting the positive electrode active material layer 16 with the positive electrode active material layer 16 (according to Figure 1 , which is the surface of the positive electrode current collector 17 in contact with the positive electrode active material layer 16) to the other surface in contact with the negative electrode active material layer 12 (according to Figure 1The electrode is intended to function as a surface where the negative electrode current collector 11 and the negative electrode active material layer 12 are in contact with each other, and there is no particular limitation as long as it is made of a conductive material, and metals and conductive resins can be used.

[0096] Specifically, electrodes having a metal selected from the group consisting of copper (Cu), tungsten (W), aluminum (Al), nickel (Ni), iron (Fe), titanium (Ti), gold (Au), silver (Ag), platinum (Pt), and palladium (Pd) can be listed. That is, as the negative electrode collector 11 and the positive electrode collector 17, electrodes consisting of a metal single substance selected from the group, an alloy containing a metal selected from the group, a metal selected from the group and a compound of carbon (C), nitrogen (N), etc. can be listed. It can be a foil coated with aluminum on the surface of stainless steel or metal. Among these, aluminum, stainless steel, copper, and nickel can be preferably used from the viewpoints of electronic conductivity, battery operating potential, cheap price, and applicability of the sputtering method that is easy to handle.

[0097] As the resin with conductivity, the resin to which conductive filler is added in the non-conductive polymer material can be preferably used. Wherein, as the non-conductive polymer material, polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyether nitrile (PEN), polyimide (PI), polyamide (PA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyvinylidene fluoride (PVdF), polystyrene (PS) can be listed. In addition, as the conductive filler, one or more metals selected from nickel (Ni), titanium (Ti), aluminum (Al), copper (Cu), platinum (Pt), chromium (Cr), iron (Fe), zinc (Zn), tin (Sn), indium (In) and antimony (Sb), alloys including these metals, metallic compounds or one or more selected from acetylene black, carbon nanofiber, carbon nanotube, carbon nanohorn, carbon nanosphere and fullerene can be listed.

[0098] The negative electrode active material layer 12 is preferably composed of graphite or a material having graphite as a main component, and more preferably composed of a material having graphite as a main component. The negative electrode active material layer 12 is preferably composed of graphite. Graphite is excellent from the viewpoints of improving the energy density of the battery, facilitating manufacturing, and reducing costs.

[0099] Here, the term "having graphite as a main component" means that the graphite is contained in a molar ratio of 90% or more and less than 100%. The material added to the graphite is a material that can absorb and store lithium ions (i.e., a material that can absorb and store lithium ions), for example, materials containing silicon and tin can be listed. As a case where the negative electrode active material layer 12 is composed of graphite and silicon, for example, a case where the molar ratio is 95% graphite and 5% silicon can be listed.

[0100] The low resistance layer 13 is a layer composed of a material containing a metal that can be alloyed with lithium (Li) (i.e., a metal that can be alloyed). For example, it is a layer composed of a lithium alloy, or a layer that is lithium alloyed by the operation of the secondary battery (charge and discharge operation). Due to the presence of the low resistance layer 13, the resistance between the negative electrode active material layer 12 and the separator layer 15 (the interface when the two are in contact) can be reduced. If the resistance between the negative electrode active material layer 12 and the separator layer 15 is reduced, the internal resistance of the secondary battery is also reduced, the charge and discharge characteristics are improved, and the capacity is also increased.

[0101] Specific materials for the low resistance layer 13 include materials containing one or more elements selected from gold (Au), silver (Ag), platinum (Pt), aluminum (Al), tin (Sn), indium (In), germanium (Ge), lead (Pb), zinc (Zn), antimony (Sb), magnesium (Mg), silicon (Si), cadmium (Cd), gallium (Ga), tellurium (Te) and bismuth (Bi). In particular, from the perspective of stability and ease of handling, it is preferred to use one or more elements selected from gold, silver, platinum, tin, indium and silicon.

[0102] In addition, the material of the low-resistance layer 13 (specifically, a material containing one or more elements selected from gold (Au), silver (Ag), platinum (Pt), aluminum (Al), tin (Sn), indium (In), germanium (Ge), lead (Pb), zinc (Zn), antimony (Sb), magnesium (Mg), silicon (Si), cadmium (Cd), gallium (Ga), tellurium (Te) and bismuth (Bi), and particularly preferably one or more elements selected from gold, silver, platinum, tin, indium and silicon) may be in any shape as long as it is in contact with the separator layer 15 so as to exert the effect of the present invention. Therefore, as long as the material is in contact with the separator layer 15 so as to exert the effect of the present invention, it is not limited to the case of being in a layered shape (specifically, the particles of the material are continuously arranged and fixed on the separator layer 15 so as to contact the separator layer as a sheet-like thin film), for example, the particles of the material may be arranged and fixed on the separator layer 15 discontinuously and bonded to the separator layer. The low-resistance layer 13 is preferably in a layered shape. This is because, in the case of a layered structure, the contact area between the separator layer 15 and the negative electrode layer 14 can be increased during charge and discharge operation, and their interface resistance is reduced, thereby improving the charge and discharge characteristics. In addition, when the thickness of the layered structure is calculated from the weight of the material used, the thickness is preferably 1 to 500 nm. In addition, it is more preferably 5 to 300 nm, and further preferably 10 to 260 nm. If it is too thin, it will not become a layered continuous film. In addition, if it is too thick, the material cost and process cost will increase, so it is preferably in the above range.

[0103] The low resistance layer 13 is preferably arranged in contact with the separator layer 15, and preferably arranged in contact with the negative electrode layer 14, especially the negative electrode active material layer 12. This is because if the low resistance layer 13 is in contact with these layers, the resistance is further reduced, and the reliability and stability of the secondary battery operation are further improved by the contact.

[0104] As a method for forming the low-resistance layer 13, one or more methods selected from the group consisting of sputtering, electron beam evaporation, thermal evaporation, and other evaporation methods, coating formation methods, and foil pasting methods can be cited. Sputtering and evaporation methods are methods commonly used in industry, and coating formation methods and foil pasting methods do not require a vacuum environment, so they are easy to handle. The low-resistance layer 13 is used to reduce the overall resistance of the interface, so it has a high tolerance for defects such as local pinholes (in other words, it is not easily affected by the defects). Therefore, the low-resistance layer 13 can be formed by low-cost methods such as foil pasting methods.

[0105] The separator layer 15 is a layer having a separator function of the all-solid lithium ion secondary battery, and contains an oxide solid electrolyte or is composed of an oxide solid electrolyte.

[0106] As the oxide solid electrolyte, garnet-type or garnet-like crystal structure electrolytes having high ion conductivity can be cited. As specific materials thereof, Li7La3Zr2O 12 , Li 7-x LqCy 2- x Ta x O 12 (wherein x is greater than or equal to 0 and less than or equal to 2), Li 7-3x La3Zr2Al x O 12 (wherein x is greater than or equal to 0 and less than or equal to 0.5), Li 7- x LqCy 2-x Nb x O 12 (wherein x is greater than or equal to 0 and less than or equal to 2) and Li 7-x-3y LqCy 2-x Ta x Al y O 12 (wherein x is greater than or equal to 0 and less than or equal to 2, and y is greater than or equal to 0 and less than or equal to 0.5).

[0107] In addition, as the solid electrolyte contained in the separator layer 15, composite oxides containing lithium (Li) and one or more ceramics selected from garnet type structure, perovskite type structure and LISICON type structure can be listed. As specific materials, LISICON, NASICON, PEO, LIPON, PVDF, Li3N, Li3P, LiI, LiBr, LiCl, LiF, Li 0.5 TiO3, Li2S-SiS2-Li3PO4, lithium nitride, doped Li3N, Li2S-SiS2-Li3PO4, Li 14 Zn(GeO4)4, Li-β-alumina, Li 3.6 Si 0.6 P 0.4 O4, PEO-LiClO4, LiN(CF3SO2)2 / (CH2CH2O)8, Li7La3Zr2O with one or more selected from Al, Ga, Nb, Ta, Ca, Sr 12 , or one or more of Li3BO3.

[0108] The positive electrode active material layer 16 is not particularly limited as long as it is a positive electrode active material containing lithium, and a typical example is a composite metal oxide containing lithium.

[0109] As specific materials for the positive electrode active material layer 16, one or more selected from the following can be cited: LiM 1 x Mn 2-x O4 (where M 1 is at least one element selected from the group consisting of Li, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Fe, Co, Ni, Cu, Al, Sn, Sb, In, Nb, Mo, W, Y, Ru and Rh, 0.01≤x≤0.5), a spinel lithium manganese composite oxide represented by Li x Mn (1-y-x) Ni y M 2 z O (2-k) F l (Among them, M 2 is at least one element selected from Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr and W, 0.8≤x≤1.2, 0<y<0.5, 0≤z≤0.5, k+l<1, -0.1≤k≤0.2, 0≤l≤0.1), a layered compound represented by LiCo 1-x M 3 x O2 (where M 3 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5), a lithium cobalt composite oxide composed of LiNi 1- x M 4 x O2 (where M 4 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5), a lithium nickel composite oxide represented by LiM 5 1-x N 1 x PO4 (where M 5 is at least one element selected from Fe, Mn and Co, N 1 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5), an olivine-type composite oxide represented by Li4Ti5O 12 Represents a lithium titanium composite oxide.

[0110] The battery having the above structure provides an all-solid lithium ion secondary battery 101 having low internal resistance and excellent charge and discharge characteristics as an all-solid lithium ion secondary battery which is one embodiment of the present invention.

[0111] <Battery manufacturing method>

[0112] First, a solid electrolyte material is sintered and molded by hot press sintering or the like, and is prepared as the separator layer 15. The sintering temperature may be, for example, 800°C or higher and 1200°C or lower.

[0113] Next, a low-resistance layer 13 is formed on one of the main surfaces (first main surface) of the separator layer 15. As a method for forming the low-resistance layer 13, as described above, one or more methods selected from a sputtering method, an electron beam evaporation method, a thermal evaporation method, a coating formation method, and a foil pasting method can be cited. It should be noted that the main surface of the separator layer in this application refers to the surface in contact with the low-resistance layer, the positive electrode active material layer, or the counter electrode.

[0114] Then, a positive electrode current collector 17 coated with a positive electrode active material layer 16 and a negative electrode current collector 11 coated with a negative electrode active material layer 12 are prepared. The materials of the positive electrode active material layer 16, the positive electrode current collector 17, the negative electrode active material layer 12 and the negative electrode current collector 11 can use the materials described in the structure of each battery. As coating methods, lamination, sputtering, evaporation, CVD (Chemical Vapor Deposition), spraying, blade coating, slit die coating, and roll coating can be listed.

[0115] Then, a negative electrode current collector 11 covered with a negative electrode active material layer 12 is arranged, a separator layer 15 is arranged in the direction where the negative electrode active material layer 12 is in contact with the low resistance layer 13, and further a positive electrode current collector 17 covered with a positive electrode active material layer 16 is arranged on the main surface of the separator layer 15 opposite to the first main surface on which the low resistance layer 13 is arranged (this main surface is referred to as the second main surface in the present application to distinguish it from the first main surface) in a manner opposite to the positive electrode active material layer 16, and after the negative electrode current collector 11, the negative electrode active material layer 12, the low resistance layer 13, the separator layer 15, the positive electrode active material layer 16 and the positive electrode current collector 17 are bundled and crimped, they are placed in a casing (not shown) to manufacture an all-solid lithium ion secondary battery 101 ( Figure 1 ).

[0116] The above-described manufacturing method can provide the all-solid lithium ion secondary battery 101 having the above-described structure. The all-solid lithium ion secondary battery 101 has the characteristics of low internal resistance and excellent charge and discharge characteristics.

[0117] Example

[0118] In the embodiment, in order to exclude the influence of the positive electrode used and purely examine the interface bonding with the graphite negative electrode active material, a full solid lithium ion half cell 102 (102) was produced using graphite as the test electrode 22, a LiLaZrTaO sintered body as the separator layer 25, and a lithium foil as the counter electrode 26. Figure 2 ), and the characteristics thereof were evaluated. The samples produced were 8 kinds of samples, namely, Examples 1 to 7 and Comparative Example 1. As for the low resistance layer 23, Examples 1 to 3 were made of gold (Au), 4 was made of indium (In), 5 was made of silver (Ag), 6 was made of platinum (Pt), and 7 was made of silicon (Si), and in Comparative Example 1, the low resistance layer 23 was not configured.

[0119] Here, the method of preparing the sample is first summarized, and then the characteristics are summarized. It should be noted that in this application, for convenience, the examples and comparative examples are sometimes referred to as "examples". In this case, Examples 1 to 7 are referred to as Examples 1 to 7, and Comparative Example 1 is referred to as Example 8.

[0120] [Preparation of samples]

[0121] <Example 1 (Example 1)>

[0122] (Solid Electrolyte)

[0123] As the separator layer 25 (solid electrolyte), a Li 6.6 Ln3Z 1.6 Ta 0.4 O 12 (Made by Toyoshima Manufacturing Co., Ltd.) Sintered body.

[0124] (Graphite dispersion)

[0125] As the graphite dispersion, a dispersion prepared by dispersing 450 mg of graphite powder (KS6 manufactured by Imerys, average diameter 4.4 μm) in 30 g of 99.5% ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used.

[0126] (Preparation process)

[0127] First, a small spraying device (manufactured by ACing Technologies, AV-8 model) was used to spray the graphite dispersion onto a non-polished SUS304 circular plate with a diameter of 10 mm and a thickness of 0.5 mm, and the coating amount was 1.77 mg / cm 2 A test electrode 22 made of graphite.

[0128] Next, using a small sputtering device (manufactured by Sanyu Electronics Co., Ltd., SC-701MkII ADVANCE), a sintered body (diameter 10 mm, thickness 2 mm) of the solid electrolyte forming the separator layer 25 was formed with a weight of 0.29 mg / cm 2 The gold layer on the side in contact with the test electrode 22 corresponds to the low resistance layer 23.

[0129] Then, a 50 μm thick lithium (Li) foil (manufactured by Honjo Chemical Co., Ltd.) is prepared as a counter electrode 26, and the lithium foil is arranged on one surface of a solid electrolyte 25 coated with a gold layer. Subsequently, a test electrode 22 made of graphite is arranged on the other surface of the solid electrolyte 25 coated with a gold layer serving as a low resistance layer 23.

[0130] Then, a test electrode 22 made of graphite, a solid electrolyte 25 coated on both sides with a gold layer, and a counter electrode 26 (Li foil) were combined to obtain a primary assembly. It should be noted that in Example 1 (Example 1), as the collector 21, SUS304 used in the sprayed substrate was used, and as the collector 27, a new non-polished SUS304 disc with a diameter of 10 mm and a thickness of 0.5 mm was placed on one surface of the counter electrode 26 (Li foil) and used.

[0131] (Pressure process)

[0132] The obtained primary assembly was screwed with a torque of 2.0 Nm to apply a restraining pressure of 40 MPa in the stacking direction, thereby obtaining the half-cell 102 of Example 1.

[0133] <Example 2 (Example 2) and Example 3 (Example 3)>

[0134] The half cells 102 of Example 2 (Example 2) and Example 3 (Example 3) were obtained in the same manner as in Example 1 (Example 1) except that the amount of graphite powder applied was changed as shown in Table 1.

[0135]

Table 1

[0136] Graphite layer Embodiment 1 (Example 1) <![CDATA[1.177mg / cm 2 ]]> Example 2 <![CDATA[1.368mg / cm 2 ]]> Example 3 <![CDATA[1.307mg / cm 2 ]]> Embodiment 4 (Example 4) <![CDATA[1.206mg / cm 2 <!-- 8 -->]]> Example 5 <![CDATA[1.239mg / cm 2 ]]> Example 6 <![CDATA[1.203mg / cm 2 ]]> Example 7 <![CDATA[1.394mg / cm 2 ]]> Comparative Example 1 (Example 8) <![CDATA[1.050mg / cm 2 ]]>

[0137] <Example 4 (Example 4)>

[0138] In Example 1 (Example 1), only one surface of the sintered body 25 of the solid electrolyte of lithium foil disposed as the counter electrode 26 was coated with a gold layer, and the other surface of the sintered body 25 of the solid electrolyte disposed with the test electrode 22 made of graphite, i.e., the surface opposite to the test electrode 22, was coated with a gold layer with a weight of 0.17 mg / cm 2The half cell 102 of Example 4 (Example 4) was obtained in the same manner as Example 1 (Example 1) except that the half cell 102 was coated with an indium (In) layer and the coating amount of the graphite powder was changed as shown in Table 1. Therefore, the low resistance layer 23 of Example 4 (Example 4) was formed of an indium layer.

[0139] <Example 5 (Example 5)>

[0140] In Example 1 (Example 1), only one surface of the sintered body 25 of the solid electrolyte of lithium foil disposed as the counter electrode 26 was coated with a gold layer, and the other surface of the sintered body 25 of the solid electrolyte disposed with the test electrode 22 made of graphite, i.e., the surface opposite to the test electrode 22, was coated with a gold layer with a weight of 0.27 mg / cm 2 The half cell 102 of Example 5 (Example 5) was obtained in the same manner as Example 1 (Example 1) except that the half cell 102 was coated with a silver (Ag) layer and the coating amount of the graphite powder was changed as shown in Table 1. Therefore, the low resistance layer 23 of Example 5 (Example 5) was formed of a silver layer.

[0141] <Example 6 (Example 6)>

[0142] In Example 1 (Example 1), only one surface of the sintered body 25 of the solid electrolyte of lithium foil disposed as the counter electrode 26 was coated with a gold layer, and the other surface of the sintered body 25 of the solid electrolyte disposed with the test electrode 22 made of graphite, i.e., the surface opposite to the test electrode 22, was coated with a gold layer with a weight of 0.41 mg / cm 2 A half cell 102 of Example 6 (Example 6) was obtained in the same manner as Example 1 (Example 1) except that the half cell 102 was coated with a platinum (Pt) layer and the coating amount of the graphite powder was changed as shown in Table 1. Therefore, the low resistance layer 23 of Example 6 (Example 6) was formed of a platinum layer.

[0143] <Example 7 (Example 7)>

[0144] In Example 1 (Example 1), only one surface of the sintered body 25 of the solid electrolyte of lithium foil disposed as the counter electrode 26 was coated with a gold layer, and the other surface of the sintered body 25 of the solid electrolyte disposed with the test electrode 22 made of graphite, i.e., the surface opposite to the test electrode 22, was coated with a gold layer at a weight of 0.06 mg / cm 2 The half cell 102 of Example 7 (Example 7) was obtained in the same manner as in Example 1 (Example 1) except that the silicon layer was coated and the coating amount of the graphite powder was changed as shown in Table 1. Therefore, the low resistance layer 23 of Example 7 (Example 7) was formed of a silicon layer.

[0145] <Comparative Example 1 (Example 8)>

[0146] A half cell of Comparative Example 1 (Example 8) was obtained in the same manner as in Example 1 (Example 1), except that only one surface of the sintered body 25 of the solid electrolyte on which the counter electrode 26 was arranged was coated with a gold layer, and the coating amount of the graphite powder was changed as shown in Table 1. Therefore, Comparative Example 1 (Example 8) did not have the low resistance layer 23.

[0147] [Characteristics evaluation]

[0148] (Initial charging test)

[0149] Using the half cells obtained in Example 1 (Example 1), Example 2 (Example 2), Examples 4 to 6 (Examples 4 to 6) and Comparative Example 1 (Example 8), a CC charge test was performed at a current value of 0.05C until the voltage became 0.01V based on lithium metal.

[0150] The initial charging curves obtained from the test results are shown in Figure 3 , Figure 5 , Fig. 9 , Fig.11 , Fig.13 and Fig.17 .

[0151] In addition, the half-cell obtained in Example 7 (Example 7) was used, and CC charging was performed at current values ​​of 0.0005C and 0.005C for 12 hours and 10 hours respectively, and then CC charging was performed at a current value of 0.05C until the voltage reached 0V based on lithium metal, and then a CV charging test was performed at 0V for 10 hours. The initial charging curve obtained as a result of the test is shown in Fig.15 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0152] (Initial charging test results)

[0153] Table 2 shows the test results of the initial charge capacity.

[0154]

Table 2

[0155] Test electrode active material Low resistance layer <![CDATA[Charge capacity (mAh / cm 2 )]]> Embodiment 1 (Example 1) graphite gold 0.437 Example 2 graphite gold 0.503 Example 3 graphite gold 0.410 Embodiment 4 (Example 4) graphite indium 0.331 Example 5 graphite silver 0.360 Example 6 graphite platinum 0.325 Example 7 graphite silicon 0.611 Comparative Example 1 (Example 8) graphite - 0.109

[0156] The weight of graphite contained in the test electrode 22 composed of graphite assembled in the half-cells obtained in Example 1 (Example 1), Example 2 (Example 2) and Comparative Example 1 (Example 8) was about 1 mg / cm 2, which are roughly equivalent. However, Example 1 (Example 1) and Example 2 (Example 2) in which a test electrode 22 made of graphite is arranged on the surface of a solid electrolyte 25 coated with a gold layer as a low resistance layer 23, obtained about 0.3 to 0.4 mAh / cm higher than Comparative Example 1 (Example 8) in which a test electrode 22 made of graphite is arranged on the surface of a solid electrolyte 25 not coated with a gold layer (not arranged with a low resistance layer 23). 2 of charging capacity.

[0157] The weight of graphite contained in the test electrode 22 composed of graphite assembled in the half-cells obtained in Example 4 (Example 4), Example 5 (Example 5), Example 6 (Example 6) and Comparative Example 1 (Example 8) was also approximately the same, but in Example 4 (Example 4), Example 5 (Example 5) and Example 6 (Example 6) in which the test electrode 22 composed of graphite was arranged on the surface of the solid electrolyte 25 coated with the indium layer, the silver layer, and the platinum layer, respectively, a higher capacity of about 0.2 to 0.3 mAh / cm was obtained than in Comparative Example 1 (Example 8) in which the test electrode 22 composed of graphite was arranged on the surface of the solid electrolyte 25 not coated with these layers. 2 That is, when an indium layer, a silver layer, or a platinum layer is configured as the low-resistance layer 23, a charge capacity of about 0.2 to 0.3 mAh / cm is obtained compared to the case where the low-resistance layer 23 is not configured. 2 of charging capacity.

[0158] Furthermore, the weight of graphite contained in the test electrode 22 composed of graphite assembled in the half-cell obtained in Example 7 (Example 7) and Comparative Example 1 (Example 8) was also substantially the same, but in Example 7 (Example 7), in which the test electrode 22 composed of graphite was arranged on the surface of the solid electrolyte 25 covered with the silicon layer as the low-resistance layer 23, CC charging was performed until 0 V was reached based on lithium metal, and then CV charging was performed for 10 hours, the obtained power was about 0.5 mAh / cm compared with Comparative Example 1 (Example 8) in which the test electrode 22 composed of graphite was arranged on the surface of the solid electrolyte 25 not covered with the silicon layer, CC charging was performed until 0 V was reached based on lithium metal, that is, no low-resistance layer 23 was arranged. 2 of charging capacity.

[0159] (AC impedance measurement method after initial charging test)

[0160] Using the half-cells obtained in Example 1 (Example 1), Example 4 (Example 4), Example 5 (Example 5), Example 6 (Example 6), Example 7 (Example 7) and Comparative Example 1 (Example 8), after the above-mentioned initial charging test, AC impedance was measured in the frequency range of 10mHz to 1MHz with the natural potential as the reference and an AC voltage of 10mV was applied.

[0161] The AC impedance spectra obtained from the test are shown in Figure 4 , Fig.10 , Fig.12 , Fig.14 , Fig.16 and Fig.18 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0162] (AC impedance measurement results after the initial charging test)

[0163] Table 3 shows the results of the AC impedance measurement after the initial charging test.

[0164]

Table 3

[0165] Test electrode active material Low resistance layer <![CDATA[Interface resistance after the first charge (Ω·cm 2 )]]> Embodiment 1 (Example 1) graphite gold 31 Embodiment 4 (Example 4) graphite indium 180 Example 5 graphite silver 330 Example 6 graphite platinum 955 Example 7 graphite silicon 67 Comparative Example 1 (Example 8) graphite - 3,188

[0166] From the AC impedance spectra obtained after the initial charge of the half-cells obtained in Example 1 (Example 1) and Comparative Example 1 (Example 8), it can be seen that in the structure without the gold layer, the interface resistance between the solid electrolyte separator layer 25 and the test electrode 22 composed of graphite is 3188Ω·cm 2 In the structure with the low resistance layer 23 composed of a gold layer, the interface resistance is reduced to 31Ω·cm 2 The interface resistance of the half-cell obtained by using the interface structure of Example 1 (Example 1) and the internal resistance of the battery cell are significantly reduced. As a result, the charge and discharge characteristics are improved, and the energy density of the battery is also improved.

[0167] In addition, from the AC impedance spectra obtained after the initial charge of the half-cells obtained in Example 4 (Example 4), Example 5 (Example 5), Example 6 (Example 6) and Example 7 (Example 7), it can be seen that for the structure sandwiching the indium (In) layer, the silver (Ag) layer, the platinum (Pt) layer, and the silicon (Si) layer, the interface resistance is 180Ω·cm 2 、330Ω·cm 2 、955Ω·cm 2 and 67Ω·cm 2 , compared with the interface resistance (3188Ω·cm) of the half-cell obtained in Comparative Example 1 (Example 8). 2 ), so it was confirmed that the interface resistance of the structure was also reduced in the same way as the structure with a gold layer.

[0168] (X-ray diffraction measurement after the initial charging test)

[0169] After the initial charging test using the half-cell 102 obtained in Example 2 (Example 2), the half-cell 102 was disassembled in a glove box under an argon atmosphere, with the surface of the graphite layer in contact with the collector 21 facing the X-ray irradiation side, and sealed in an atmosphere separator for X-ray diffraction (manufactured by Rigaku) ​​(argon atmosphere), and an X-ray diffraction device (manufactured by Rigaku, Miniflex600) was used to perform X-ray diffraction measurement in the diffraction angle range of 20° to 30° (2θ). The X-ray diffraction pattern obtained as a result of the test is shown in Figure 6 .

[0170] (X-ray diffraction measurement results after the initial charging test)

[0171] From the X-ray diffraction pattern of the half-cell 102 obtained in Example 2 (Example 2) after the initial charge, it can be seen that the gold layer reacts with lithium and changes into the alloy Li3Au. It can be seen that the volume expansion during the alloying reaction contributes greatly to the phenomenon of reducing the interface resistance in the structure in which the gold layer as the low resistance layer 23 is sandwiched by the test electrode 22 and the separator layer 25. In addition, it can be seen that by reducing the interface resistance, lithium is inserted into the graphite contained in the graphite layer near the collector from the charging state of stage 2 to 1 during CC charging with a current value of 0.05C at room temperature.

[0172] (Charge and discharge cycle test)

[0173] Using the half cell 102 obtained in Example 3 (Example 3), a charge and discharge test was performed at a voltage range of 0.01 to 1.2 V based on lithium metal and a current value of 0.05 C. The initial charge and discharge curve obtained as a result of the test is shown in Figure 7 The battery capacity relative to the number of charge and discharge cycles up to 20 cycles is shown in Figure 8 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0174] (Charge and discharge cycle test results)

[0175] From the initial charge and discharge curve of the half-cell 102 obtained in Example 3 (Example 3), it can be seen that no large hysteresis is found in the charge and discharge curve, and it can be seen that the initial coulombic efficiency is also a value exceeding 70%. In the second and subsequent cycles, high reversibility is found, and no significant capacity decrease is found. Therefore, it can be seen that the half-cell 102 obtained using the interface structure disclosed in the present invention not only shows high energy density, but also shows high stability.

[0176] Furthermore, as shown below, examples 9 to 20 are added. The samples trial-produced in the additional examples are 12 kinds of samples from examples 9 to 20. In the additional examples, in order to exclude the influence of the positive electrode used and purely examine the interface bonding with the graphite negative electrode active material, a full solid lithium ion half cell 102 (including a material having graphite as a main body) was trial-produced using graphite as the test electrode 22, a LiLaZrTaO sintered body as the separator layer 25, and a lithium foil as the counter electrode 26. Figure 2 ), and its characteristics were evaluated. As for the low resistance layer 23, Examples 9 and 10, and Examples 17 to 20 were composed of gold (Au), Examples 11 and 12 were composed of indium (In), Examples 13 and 14 were composed of silver (Ag), and Examples 15 and 16 were composed of platinum (Pt). In Example 17, the test electrode 22 was not configured, and in Example 18, the test electrode 22 composed of graphite and silicon was assembled, and a half-cell was trial-produced to evaluate its characteristics.

[0177] Examples 19 and 20 are negative electrodes produced experimentally for evaluating the element distribution in the thickness direction of the test electrode 22. In Example 19, the test electrode 22 is made of graphite, and in Example 20, it is made of graphite and silicon.

[0178] Here, as in the above-mentioned embodiments (i.e., Examples 1 to 8), the method for preparing the samples is first summarized, and then the characteristics are summarized. In this case, for comparison, Example 3 (i.e., Example 3) and Example 8 (i.e., Comparative Example 1) described in the above-mentioned embodiments are also used as appropriate.

[0179] [Preparation of samples]

[0180] <Example 9>

[0181] (Solid Electrolyte)

[0182] As the separator layer 25 (solid electrolyte), a Li 6.6 LqCy 1.6 Ta 0.4 O 12 (Made by Toyoshima Manufacturing Co., Ltd.) Sintered body.

[0183] (Graphite dispersion)

[0184] As the graphite dispersion, a dispersion prepared by dispersing 450 mg of graphite powder (KS6 manufactured by Imerys, average diameter 4.4 μm) in 30 g of 99.5% ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used.

[0185] (Preparation process)

[0186] First, a small spraying device (manufactured by ACing Technologies, AV-8 model) was used to spray the graphite dispersion onto a non-polished SUS304 circular plate with a diameter of 10 mm and a thickness of 0.5 mm, and the coating amount was 1.231 mg / cm 2 A test electrode 22 made of graphite.

[0187] Next, using a small sputtering device (manufactured by Sanyu Electronics Co., Ltd., SC-701MkII ADVANCE), a sintered body (diameter 10 mm, thickness 2 mm) of the solid electrolyte forming the separator layer 25 was formed with a weight of 0.29 mg / cm 2 The gold layer on the side in contact with the test electrode 22 corresponds to the low resistance layer 23. Therefore, the low resistance layer 23 of Example 9 is formed of a gold layer with a thickness of 150 nm.

[0188] Then, a 50 μm thick lithium (Li) foil (manufactured by Honjo Chemical Co., Ltd.) is prepared as a counter electrode 26, and the lithium foil is arranged on one surface of a solid electrolyte 25 coated with a gold layer. Subsequently, a test electrode 22 made of graphite is arranged on the other surface of the solid electrolyte 25 coated with a gold layer serving as a low resistance layer 23.

[0189] Then, a test electrode 22 made of graphite, a solid electrolyte 25 coated on both sides with a gold layer, and a counter electrode 26 (Li foil) were combined to obtain a primary assembly. It should be noted that in Example 9, as the collector 21, SUS304 used in the sprayed substrate was used, and as the collector 27, a new non-polished SUS304 disc with a diameter of 10 mm and a thickness of 0.5 mm was placed on one surface of the counter electrode 26 (Li foil) and used.

[0190] (Pressure process)

[0191] The obtained primary assembly was screwed with a torque of 2.0 Nm, thereby applying a restraining pressure of 40 MPa in the stacking direction, thereby obtaining the half-cell 102 of Example 9.

[0192]

Table 4

[0193]

[0194] <Example 10>

[0195] In addition to the fact that in Example 9 the surface opposite to the test electrode 22 made of graphite was coated with a weight of 0.05 mg / cm 2 The half cell 102 of Example 10 was obtained in the same manner as in Example 9 except that the half cell 102 was coated with a gold (Au) layer of 26 nm and the coating amount of the graphite powder was changed as shown in Table 4. Therefore, the low resistance layer 23 of Example 10 was formed of a gold layer with a thickness of 26 nm.

[0196]

Table 5

[0197]

[0198] <Example 11>

[0199] In Example 9, only one surface of the sintered body 25 of the solid electrolyte of lithium foil disposed as the counter electrode 26 was coated with a gold layer, and the other surface of the sintered body 25 of the solid electrolyte disposed with the test electrode 22 made of graphite, i.e., the surface opposite to the test electrode 22, was coated with a gold layer with a weight of 0.08 mg / cm 2 The half cell 102 of Example 11 was obtained in the same manner as in Example 9 except that the indium (In) layer was coated and the coating amount of the graphite powder was changed as shown in Table 4. Therefore, the low resistance layer 23 of Example 11 was formed of an indium layer with a thickness of 109 nm.

[0200] <Example 12>

[0201] In Example 11, the surface of the solid electrolyte sintered body 25 facing the test electrode 22 made of graphite was sintered with a weight of 0.01 mg / cm 2 The half cell 102 of Example 12 was obtained in the same manner as in Example 11 except that the indium (In) layer was coated and the coating amount of the graphite powder was changed as shown in Table 4. Therefore, the low resistance layer 23 of Example 12 was formed of an indium layer with a thickness of 14 nm.

[0202] <Example 13>

[0203] In Example 9, only one surface of the sintered body 25 of the solid electrolyte of lithium foil disposed as the counter electrode 26 was coated with a gold layer, and the other surface of the sintered body 25 of the solid electrolyte disposed with the test electrode 22 made of graphite, i.e., the surface opposite to the test electrode 22, was coated with a gold layer with a weight of 0.11 mg / cm 2 The half cell 102 of Example 13 was obtained in the same manner as in Example 9 except that the half cell 102 was coated with a silver (Ag) layer of 104 nm and the coating amount of the graphite powder was changed as shown in Table 4. Therefore, the low resistance layer 23 of Example 13 was formed of a silver layer with a thickness of 104 nm.

[0204] <Example 14>

[0205] In Example 13, the surface of the sintered body 25 of the solid electrolyte facing the test electrode 22 made of graphite was sintered with a weight of 0.03 mg / cm 2 The half cell 102 of Example 14 was obtained in the same manner as in Example 13 except that the silver (Ag) layer was coated and the coating amount of the graphite powder was changed as shown in Table 4. Therefore, the low resistance layer 23 of Example 14 was formed of a silver layer with a thickness of 29 nm.

[0206] <Example 15>

[0207] In Example 9, only one surface of the sintered body 25 of the solid electrolyte of lithium foil disposed as the counter electrode 26 was coated with a gold layer, and the other surface of the sintered body 25 of the solid electrolyte disposed with the test electrode 22 made of graphite, i.e., the surface opposite to the test electrode 22, was coated with a gold layer at a weight of 0.16 mg / cm 2 The half cell 102 of Example 15 was obtained in the same manner as in Example 9 except that the coating amount of the graphite powder was changed as shown in Table 4. Therefore, the low resistance layer 23 of Example 15 was formed of a platinum layer with a thickness of 75 nm.

[0208] <Example 16>

[0209] In Example 15, the surface of the solid electrolyte sintered body 25 facing the test electrode 22 made of graphite was sintered with a weight of 0.04 mg / cm 2 The half cell 102 of Example 16 was obtained in the same manner as in Example 15 except that the coating amount of the graphite powder was changed as shown in Table 4. Therefore, the low resistance layer 23 of Example 16 was formed of a platinum layer with a thickness of 19 nm.

[0210] <Example 17>

[0211] In Example 9, the weight of the gold layer of the low-resistance layer 23 was changed to 0.34 mg / cm 2 The current collector 21 was arranged outside the partition wall of the gold layer serving as the low resistance layer 23, and the half cell 102 of Example 17 was obtained in the same manner as in Example 9. Therefore, Example 17 did not have the test electrode 22, and the low resistance layer 23 was formed of a gold layer with a thickness of 175 nm.

[0212] <Example 18>

[0213] In Example 9, the graphite dispersion was changed to a graphite-silicon dispersion for spraying, and the assembled coating amount was 1.37 mg / cm 2 A half-cell 102 of Example 18 was obtained in the same manner as in Example 9 except that the test electrode 22 composed of graphite and silicon was used and the weight of the gold layer of the resistance reducing layer 23 was changed as shown in Table 5.

[0214] (Graphite-Silicon Dispersion)

[0215] As the graphite-silicon dispersion, a dispersion obtained by dispersing 450 mg of graphite powder (manufactured by Imerys, KS6, average diameter 4.4 μm) and 45 mg of 50 nm diameter silicon powder (manufactured by Alfa Aesar) in 30 g of 99.5% ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used. The molar ratio of the dispersed graphite to the silicon was 95:5.

[0216] <Example 19>

[0217] Except for changing the coating amount of graphite powder as shown in Table 4, a negative electrode (negative electrode layer) consisting only of a test electrode 22 made of graphite and a collector 21 which is an unpolished SUS304 disc with a diameter of 10 mm and a thickness of 0.5 mm was obtained in the same manner as in Example 9.

[0218] <Example 20>

[0219] In addition to changing the coating amount of the test electrode 22 composed of graphite and silicon to 1.717 mg / cm 2 In the same manner as in Example 18, a negative electrode (negative electrode layer) was obtained which consisted of only a test electrode 22 made of graphite and silicon and a current collector 21 which was an unpolished SUS304 disk having a diameter of 10 mm and a thickness of 0.5 mm.

[0220] [Characteristics evaluation]

[0221] (Initial charging test)

[0222] The half-cells 102 obtained in Examples 9, 10 to 16, 18, and 8 were used to perform a CC charge test at a current value of 0.05C until the voltage reached 0.01V based on lithium metal. The value of each C rate was calculated from the amount of graphite applied to the test electrode 22. For the half-cell obtained in Example 18, the graphite and silicon dispersed in the graphite-silicon dispersion used for spraying were applied while maintaining a weight ratio of 10:1. The amount of graphite applied (estimated to be 1.243 mg / cm 2 ) is calculated.

[0223] The initial charging curves obtained from the test results are shown in Fig.19 , Fig. 22 , Fig.24 , Fig.26 , Fig.28 , Fig.30 , Fig.32 and Fig.34 .

[0224] In addition, the half-cell 102 obtained in Example 7 was used, and CC charging was performed at current values ​​of 0.0005C and 0.005C for 12 hours and 10 hours respectively, and then CC charging was performed at a current value of 0.05C until the voltage reached 0V based on lithium metal, and then a CV charging test was performed at 0V for 10 hours. The initial charging curve obtained as a result of the test is shown in Fig.15 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0225] (Initial charging test results)

[0226] Table 6 shows the test results of the initial charge capacity.

[0227]

Table 6

[0228]

[0229] The weight of graphite contained in the test electrode 22 composed of graphite assembled in the half-cell 102 obtained in Examples 9, 10 and 8 is about 1 mg / cm 2 However, in Examples 9 and 10, where a test electrode 22 made of graphite was arranged on the surface of a solid electrolyte 25 coated with a gold layer as a low-resistance layer 23, the obtained performance was about 0.2 to 0.4 mAh / cm higher than that of Example 8, where a test electrode 22 made of graphite was arranged on the surface of a solid electrolyte 25 not coated with a gold layer (not arranged with a low-resistance layer 23). 2 of charging capacity.

[0230] It can also be seen that the weight of graphite contained in the test electrode 22 composed of graphite and silicon assembled in the half-cell 102 obtained in Example 18 and the weight of the gold layer of the low-resistance layer 23 are approximately the same as the weight of graphite contained in the test electrode 22 composed of graphite assembled in the half-cell obtained in Example 9 and the weight of the gold layer of the low-resistance layer 23, respectively. However, compared with Example 9, in Example 18, nearly twice the charging capacity was obtained.

[0231] The weight of graphite contained in the test electrode 22 composed of graphite assembled in the half-cell 102 obtained in Examples 11 to 16 and Example 8 is also approximately the same. However, in Examples 11 to 16, in which the test electrode 22 composed of graphite is arranged on the surface of the solid electrolyte 25 coated with the indium layer, the silver layer, and the platinum layer, respectively, the test electrode 22 composed of graphite is arranged on the surface of the solid electrolyte 25 not coated with these layers, which is about 0.2 to 0.3 mAh / cm2 higher than that in Example 8, in which the test electrode 22 composed of graphite is arranged on the surface of the solid electrolyte 25 not coated with these layers. 2 That is, when an indium layer, a silver layer, or a platinum layer is configured as the low-resistance layer 23, a charge capacity of about 0.2 to 0.3 mAh / cm is obtained compared to the case where the low-resistance layer 23 is not configured. 2 of charging capacity.

[0232] Furthermore, although the weight of graphite contained in the test electrode 22 composed of graphite assembled in the half-cell 102 obtained in Examples 7 and 8 was also approximately the same, in Example 14, in which the test electrode 22 composed of graphite was arranged on the surface of the solid electrolyte 25 covered with a silicon layer as the low-resistance layer 23, CC charging was performed until 0 V was reached based on lithium metal, and then CV charging was performed for 10 hours, the obtained power was about 0.5 mAh / cm compared with that in Example 8, in which the test electrode 22 composed of graphite was arranged on the surface of the solid electrolyte 25 not covered with a silicon layer, and CC charging was performed until 0 V was reached based on lithium metal, that is, no low-resistance layer 23 was arranged. 2 of charging capacity.

[0233] (AC impedance measurement method after initial charging test)

[0234] The half-cell 102 obtained in Examples 9, 10 to 16, 7, 18 and 8 was used to carry out the above-mentioned initial charging test, and then AC impedance was measured in the frequency range of 10 mHz to 1 MHz with natural potential as the reference and an AC voltage of 10 mV applied.

[0235] The AC impedance spectra obtained from the test are shown in Fig. 20 , Fig.23 , Fig.25 , Fig. 27 , Fig.29 , Fig.31 , Fig.33 , Fig.35 , Fig.16 , Fig.39 and Fig.18 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0236] (AC impedance measurement results after the initial charging test)

[0237] Table 7 shows the results of the AC impedance measurement after the initial charging test.

[0238]

Table 7

[0239]

[0240] From the AC impedance spectra obtained after the initial charge of the half-cell 102 obtained in Examples 9, 10 and Example 8, it can be seen that in the structure without the gold layer, the interface resistance between the solid electrolyte separator layer 25 and the test electrode 22 composed of graphite is 3188Ω·cm 2 In the structure with the low resistance layer 23 composed of a gold layer, the interface resistance is reduced to about 30Ω·cm 2 The interface resistance of the half-cell and the internal resistance of the battery cell obtained by using the interface structure of Example 9 are significantly reduced. As a result, the charge and discharge characteristics are improved and the energy density of the battery is also improved.

[0241] From the AC impedance spectra obtained after the initial charge of the half-cell 102 obtained in Examples 11 to 16 and Example 7, it can be seen that for the structure sandwiching the indium (In) layer, the silver (Ag) layer, the platinum (Pt) layer, and the silicon (Si) layer, the interface resistance is about 20 to 70 Ω·cm 2 , compared with the interface resistance (3188Ω·cm) of the half-cell obtained in Comparative Example 1 (Example 8). 2 ), so it was confirmed that the interface resistance of the structure was also reduced in the same way as the structure with a gold layer.

[0242] It can also be seen that the low-resistance layer 23 assembled in the half-cell 102 obtained in Examples 10, 12, 14 and 16 is formed by a metal layer with a thickness of 10 to 30 nm, but shows a low interface resistance roughly equivalent to that of Examples 9, 11, 13 and 15 in which the low-resistance layer 23 is assembled with a corresponding metal layer with a thickness of 100 to 200 nm.

[0243] Furthermore, from the AC impedance spectrum obtained after the initial charge of the half-cell 102 obtained in Example 18, it can be seen that in the structure in which the low-resistance layer 23 composed of a gold layer is sandwiched, the interface resistance between the solid electrolyte separator layer 25 and the test electrode 22 composed of graphite and silicon is 20Ω·cm, which is approximately the same as that of the half-cells obtained in Examples 9 and 10. 2 .

[0244] (X-ray diffraction measurement after the initial charging test)

[0245] After the initial charging test using the half-cell 102 obtained in Examples 9 and 18, the half-cell 102 was disassembled in a glove box under an argon atmosphere, with the surface of the graphite layer in contact with the collector 21 facing the X-ray irradiation side, and sealed in an atmosphere separator for X-ray diffraction (manufactured by Rigaku) ​​(argon atmosphere), and an X-ray diffraction device (manufactured by Rigaku, Miniflex600) was used to perform X-ray diffraction measurement in the diffraction angle range of 20° to 30° (2θ). The X-ray diffraction patterns obtained as a result of the test are shown in Figure 5 and Fig.28 .

[0246] (X-ray diffraction measurement results after the initial charging test)

[0247] From the X-ray diffraction pattern after the initial charge of the half-cell 102 obtained in Example 9, it can be seen that the gold layer reacts with lithium and changes into the alloy Li3Au. It can be seen that the volume expansion during the alloying reaction contributes greatly to the phenomenon of reducing the interface resistance in the structure in which the gold layer as the low resistance layer 23 is sandwiched by the test electrode 22 and the separator layer 25. In addition, it can be seen that by reducing the interface resistance, lithium is inserted into the graphite contained in the graphite layer near the collector until the charging state of stage 2 during CC charging with a current value of 0.05C at room temperature.

[0248] From the X-ray diffraction pattern of the half-cell 102 obtained in Example 18 after the initial charge, it can be seen that, as in Example 9, the gold layer reacts with lithium and changes into the alloy Li3Au. It can be seen that, in the structure in which the gold layer as the low-resistance layer 23 is sandwiched between the test electrode 22 and the separator layer 25, the phenomenon of reducing the interface resistance is confirmed, and the volume expansion during the alloying reaction also contributes greatly. However, unlike Example 9, it can be seen that in the CC charging using a current value of 0.05C at room temperature, lithium is inserted into the graphite contained in the graphite-silicon layer near the collector until the charging state of stage 1. Since no peak from crystalline silicon is observed, it can be seen that the silicon contained in the test electrode 22 reacts with lithium and changes into an amorphous lithium alloy. It can be seen that, in the structure in which the metal that alloys with lithium and changes in volume is included in the test electrode 22, the phenomenon of deepening the charging depth of graphite is confirmed, and the volume expansion during the alloying reaction contributes greatly.

[0249] (Measurement of element distribution in the depth direction of the negative electrode layer)

[0250] The negative electrode layer composed of the test electrode 22 and the current collector 21 obtained in Examples 19 and 20 was subjected to element distribution measurement in the depth direction using a glow discharge luminescence analyzer (GD-Profiler2 manufactured by Horiba, Ltd.). The element distribution in the depth direction obtained as a result of the test is shown in Fig.41 and Fig.42 Sputtering was performed in a pulsed manner, using a mixed gas of argon (Ar) and oxygen (O2) at a volume ratio of 95:5 as the sputtering gas. The sputtering area was 4 mm in diameter.

[0251] (Measurement Results of Element Distribution in the Depth Direction of the Negative Electrode Layer)

[0252] According to the element distribution in the depth direction of the negative electrode layer obtained in Example 19, the iron (Fe) signal, which is the signal from the SUS disc of the collector 21, is almost unobservable until slightly before the carbon (C) signal begins to decrease, so it can be seen that the test electrode 22 becomes a graphite particle stack of uniform thickness.

[0253] As for the element distribution in the depth direction of the negative electrode layer obtained in Example 20, the signal of iron (Fe), which is the signal from the SUS disk of the collector 21, is hardly observed until slightly before the signal of carbon (C) begins to decrease, so it can be seen that the test electrode 22 is a graphite particle stack of uniform thickness. In addition, as for the signal of silicon (Si), it is continuously observed with a certain intensity until the signal of carbon begins to decrease, so it can be seen that silicon is uniformly distributed in the test electrode 22.

[0254] (Initial charging test of low resistance layer)

[0255] The half cell 102 obtained in Example 17 was used to generate a current of 23.7 μA / cm 2 The CC charging test was performed until the voltage reached 0.01 V based on lithium metal. The current value and the coating amount of 1.274 mg / cm when 1.00 mg of graphite was coated on the collector 21 with a diameter of 10 mm 2 The current value of the test electrode 22 made of graphite at 0.05C is the same. That is, it is substantially the same as the current value used in Example 9. The initial charging curve obtained as a result of the test is shown in Fig.36 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0256] (Results of the initial charging test of the low resistance layer)

[0257] In the half-cell 102 obtained in Example 17, the test electrode 22 made of graphite was not assembled, but the gold layer as the low-resistance layer 23 reacted with lithium to form an alloy, thereby obtaining a 0.154 mAh / cm 2 of charging capacity.

[0258] (Method for measuring AC impedance of low resistance layer after initial charging test)

[0259] The half-cell 102 obtained in Example 17 was used to perform the above-mentioned initial charge test, and then AC impedance measurement was performed in the frequency range of 10 mHz to 1 MHz with the natural potential as the reference and an AC voltage of 10 mV applied.

[0260] The AC impedance spectrum obtained from the test is shown in Fig.37 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0261] (Results of AC impedance measurement after the initial charging test of the low resistance layer)

[0262] The interface resistance obtained from the AC impedance measurement results after the initial charge test was 31 Ω·cm 2 When a gold layer was used as the resistance reducing layer 23, it was found that the interface resistance was substantially the same as that of the half-cells obtained in Examples 9 and 10 in which the test electrodes 22 made of graphite were assembled.

[0263] (Initial charge capacity of graphite layer)

[0264] The half cell 102 obtained in Example 9 was assembled with a test electrode 22 made of graphite that reacts with lithium and a gold layer as a low resistance layer 23. Therefore, in the obtained 0.513 mAh / cm 2The charge capacity includes the capacity of the two active materials. The half-cell obtained in Example 17 is assembled with only the gold layer as the low resistance layer 23, and its weight is roughly the same as that of Example 9. Therefore, the charge capacity shown in the half-cell obtained in Example 17 is 0.154 mAh / cm 2 The charge capacity of the half-cell obtained in Example 9 can be regarded as the charge capacity of the gold layer as the low resistance layer 23. That is, in the half-cell 102 obtained in Example 9, the charge capacity of the test electrode 22 composed of graphite is 0.359 mAh / cm 2 (=0.513mAh / cm 2 -0.154mAh / cm 2 ), it can be seen that it is possible to charge with a weight capacity density of 291 mAh / g.

[0265] (Initial charge capacity of graphite-silicon layer)

[0266] The half-cell 102 obtained in Example 18 was assembled with a test electrode 22 made of graphite and silicon that react with lithium and a gold layer as a low-resistance layer 23. 2 The charge capacity includes the capacity of three active materials. The half-cell obtained in Example 17 is assembled with only the gold layer as the low resistance layer 23, and its weight is roughly the same as that of Example 9. Therefore, the charge capacity shown in the half-cell 102 obtained in Example 17 is 0.154 mAh / cm 2 The charge capacity of the half-cell 102 obtained in Example 18 can be regarded as the charge capacity of the gold layer as the low resistance layer 23. That is, in the half-cell 102 obtained in Example 18, the charge capacity of the test electrode 22 composed of graphite and silicon is 0.970 mAh / cm 2 (=1.124mAh / cm 2 -0.154mAh / cm 2 ). In addition, the amount of silicon applied was estimated by applying the graphite and silicon dispersed in the graphite-silicon dispersion used for spraying at a weight ratio of 10:1, and the charge capacity calculated by charging the silicon to the theoretical capacity was 0.525 mAh / cm 2 When the charge capacity shown by silicon of the test electrode 22 is considered, the charge capacity shown by graphite of the test electrode 22 is 0.445 mAh / cm 2 , it can be seen that charging with a weight capacity density of 359 mAh / g is possible.

[0267] From the weight capacity density shown by the test electrode 22 composed of only graphite in the half-cell 102 obtained in Example 9, it can be seen that the graphite contained in the test electrode 22 in which graphite and silicon are mixed at a molar ratio of 95:5 in the half-cell 102 obtained in Example 18 shows a large weight capacity density close to the theoretical capacity. This is consistent with the result that the X-ray diffraction pattern measured after the initial charge shows that lithium is inserted into the graphite until the charging state of stage 1.

[0268] From the results of the element distribution measurement in the depth direction of the negative electrode layer, silicon is uniformly distributed in the test electrode 22 composed of graphite and silicon, which is produced by spraying a graphite-silicon dispersion. In addition, from the results of the X-ray diffraction measurement after the initial charge, it can be seen that the silicon contained in the test electrode 22 reacts with lithium after charging and changes into an amorphous silicon alloy. It can be seen from this that the phenomenon that the graphite in the test electrode 22 in which silicon is mixed in the graphite shows a large weight capacity density compared to the weight capacity density shown by the graphite in the test electrode 22 composed of only graphite is that the volume expansion during the alloying reaction of silicon and the network formation in the test electrode 22 caused by the bonding between the alloy particles found in Patent Document 2 and Non-Patent Document 2 contribute greatly.

[0269] (Charge and discharge cycle test)

[0270] Using the half cell 102 obtained in Example 3, a charge and discharge test was performed at a voltage range of 0.01 to 1.2 V based on lithium metal and a current value of 0.05 C. The initial charge and discharge curve obtained as a result of the test is shown in FIG. Figure 7 The battery capacity relative to the number of charge and discharge cycles up to 20 cycles is shown in Figure 8 The test environment was an argon atmosphere at room temperature of about 25°C under atmospheric pressure.

[0271] (Charge and discharge cycle test results)

[0272] From the initial charge and discharge curve of the half-cell 102 obtained in Example 3, it can be seen that no large hysteresis is found in the charge and discharge curve, and it can be seen that the initial coulombic efficiency is also a value exceeding 70%. In the second and subsequent cycles, high reversibility is found, and no significant capacity decrease is found, so it can be seen that the half-cell 102 obtained using the interface structure disclosed in the present invention not only shows high energy density, but also shows high stability.

[0273] Industrial Applicability

[0274] The present invention relates to an all-solid lithium ion secondary battery that is expected to be used as a next-generation secondary battery for electric vehicles, submarines, homes and industries including hybrid power from the perspectives of electric capacity, charge-discharge and high current characteristics, miniaturization and safety. According to the present invention, an all-solid lithium ion secondary battery with low internal resistance and excellent charge-discharge characteristics is provided. Therefore, it is believed that the present invention makes a great contribution to the development of the industry.

[0275] Description of Reference Numerals

[0276] 11: Negative electrode collector

[0277] 12: Negative electrode active material layer (e.g. graphite)

[0278] 13: Low resistance layer

[0279] 14: Negative electrode (negative electrode layer)

[0280] 15: Separator layer (all-solid electrolyte layer, solid electrolyte, sintered body)

[0281] 16: Positive electrode active material layer

[0282] 17: Positive electrode collector

[0283] 18: Positive electrode (positive electrode layer)

[0284] 21: Current Collector

[0285] 22: Test electrode (such as graphite)

[0286] 23: Low resistance layer

[0287] 25: Separator layer (all-solid electrolyte layer, solid electrolyte, sintered body)

[0288] 26: Counter electrode (lithium foil)

[0289] 27: Current Collector

[0290] 101: All-solid-state lithium-ion secondary battery

[0291] 102: All-solid lithium-ion half-cell

Claims

1. An all-solid lithium ion secondary battery, comprising at least a negative electrode layer, a separator layer, and a positive electrode layer, wherein the negative electrode layer comprises a negative electrode active material comprising graphite, the separator layer comprises an oxide solid electrolyte, a low resistance layer is formed between the negative electrode layer and the separator layer, the low resistance layer is composed of a lithium alloy, or has a material that forms a lithium alloy by performing a secondary battery operation in which a current flows between the negative electrode layer and the positive electrode layer.

2. The all-solid lithium ion secondary battery according to claim 1, wherein: The low resistance layer includes one or more elements selected from the group consisting of gold, silver, platinum, aluminum, tin, indium, germanium, lead, zinc, antimony, magnesium, silicon, cadmium, gallium, tellurium, and bismuth.

3. The all-solid lithium ion secondary battery according to claim 1, wherein: The low resistance layer has a thickness of 1 to 500 nm.

4. The all-solid lithium ion secondary battery according to claim 1, wherein: The resistance reducing layer includes one or more selected from the group consisting of gold, silver, platinum, tin, indium, and silicon.

5. The all-solid lithium ion secondary battery according to any one of claims 1 to 4, wherein The resistance reducing layer is arranged in contact with the separator layer.

6. The all-solid lithium ion secondary battery according to any one of claims 1 to 5, wherein The resistance reducing layer is arranged in contact with the negative electrode layer.

7. The all-solid lithium ion secondary battery according to any one of claims 1 to 6, wherein The solid electrolyte contained in the separator layer has a garnet-type or garnet-type-like crystal structure having high ion conductivity.

8. The all-solid lithium ion secondary battery according to any one of claims 1 to 7, wherein The solid electrolyte contained in the separator layer is composed of a composite oxide containing Li and one or more selected from the group consisting of ceramics having a garnet type structure, ceramics having a perovskite type structure, and ceramics having a LISICON type structure.

9. The all-solid lithium ion secondary battery according to any one of claims 1 to 8, wherein The negative electrode active material is composed of graphite.

10. The all-solid lithium ion secondary battery according to any one of claims 1 to 9, wherein The negative electrode active material includes graphite and a material capable of absorbing less than 10% of lithium ions.

11. The all-solid lithium ion secondary battery according to any one of claims 1 to 10, wherein: The positive electrode comprises a positive electrode active material, and the positive electrode active material is composed of one or more selected from the following: By LiM 1 x Mn 2-x A spinel lithium manganese composite oxide represented by O4, wherein M 1 is at least one element selected from the group consisting of Li, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Fe, Co, Ni, Cu, Al, Sn, Sb, In, Nb, Mo, W, Y, Ru and Rh, 0.01≤x≤0.5, By Li x Mn (1-y-x) Ni y M 2 z O (2-k) F l The layered compound shown, where M 2 is at least one element selected from Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr and W, 0.8≤x≤1.2, 0<y<0.5, 0≤z≤0.5, k+l<1, -0.1≤k≤0.2, 0≤l≤0.1, By LiCo 1-x M 3 x A lithium cobalt composite oxide represented by O2, wherein M 3 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5, By LiNi 1-x M 4 x A lithium nickel composite oxide represented by O2, wherein M 4 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5, By LiM 5 1-x N 1 x PO4 represented by an olivine-type composite oxide, wherein M 5 is at least one element selected from Fe, Mn and Co, N 1 is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≤x≤0.5, Li4Ti5O 12 The lithium titanium composite oxide shown.

12. A method for manufacturing an all-solid lithium ion secondary battery according to any one of claims 1 to 11, wherein: The resistance reducing layer is formed by one or more methods selected from the group consisting of a sputtering method, a vapor deposition method, a coating method, and a foil pasting method.